2021
DOI: 10.3390/ijerph18116130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Quality Perception on Depression: Subjective Social Class as a Mediator

Abstract: Although the relationship between environment and public depression has aroused heated debate, the empirical research on the relationship between environmental quality perception and public depression is still relatively insufficient. This paper aims to explore the influence of environmental quality perception on public depression and the mediating role of subjective social class between environmental quality perception and public depression. Using the China Family Panel Studies data of 2016 for empirical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…People with lower psychological security might experience negative emotions and mental disorders [32]. As a result, the public's negative perception of environmental quality may induce a negative mentality when they are in the environment [33]. In the literature, it was found that annoyance caused by the environment such as noise and air pollution was associated with lower sleep quality and mental disorders for residents [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…People with lower psychological security might experience negative emotions and mental disorders [32]. As a result, the public's negative perception of environmental quality may induce a negative mentality when they are in the environment [33]. In the literature, it was found that annoyance caused by the environment such as noise and air pollution was associated with lower sleep quality and mental disorders for residents [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Five epidemiologic studies used qualitative methods [ 43 , 214 , 231 , 243 , 244 ], spanning topics from urban flooding in Detroit [ 244 ], industrial mining in Burkina Faso, Mozambique, and Tanzania [ 231 ], and environmental and reproductive justice on the Gulf Coast of the US [ 43 ]. Finally, five epidemiologic studies used formal mediation analyses to determine if environmental factors mediated the observed relationship between health disparity factors (e.g., poverty) and adverse health outcomes [ 42 , 207 , 252 254 ]. In Bangladesh, Huang et al considered serum metals as a mediator between childhood marriage and preterm birth, finding that elevated levels of zinc, arsenic, strontium, and barium appeared to mediate the association between childhood marriage and preterm birth [ 252 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the varying degrees of acceptance or stigmatization of vegetarianism in different cultural contexts could explain the variability in the psychological effects of this dietary pattern. Another possible explanation is that the emotional burden of ethical or environmental concerns often motivates vegetarianism [ 38 , 39 ], these factors may contribute to a higher level of psychological stress, which could worsen or present as symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%